2010
DOI: 10.1001/dmp.2010.11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hurricane Katrina on Nursing Facility Resident Mortality, Hospitalization, and Functional Decline

Abstract: ABSTRACTBackground: The study was designed to examine the 30- and 90-day mortality and hospitalization rates among nursing facility (NF) residents in the affected areas of Louisiana and Mississippi following Hurricane Katrina and to assess the rate of significant posthurricane functional decline.Methods: A secondary data analysis was conducted using Medicare claims merged with NF resident data from the Minimum Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 18 publications
(37 reference statements)
4
69
0
2
Order By: Relevance
“…Finally, NHs from counties/parishes where there were no known evacuations were removed. 4 The geographic exposure region for each of the four storms is available from the author.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, NHs from counties/parishes where there were no known evacuations were removed. 4 The geographic exposure region for each of the four storms is available from the author.…”
Section: Methodsmentioning
confidence: 99%
“…Less than a month later, 72 facilities evacuated in the same region prior to Hurricane Rita. 4 In 2008, 119 facilities evacuated prior to Hurricane Gustav and 81 facilities evacuated prior to Hurricane Ike, even though it made landfall far south of the evacuated Louisiana facilities. i …”
Section: Introductionmentioning
confidence: 99%
“…Dosa and colleagues found that evacuation, and not storm effects experienced while sheltering in place, contributed significantly to increased rates of hospitalization, morbidity, and mortality of nursing home residents. 2,6 …”
Section: Introductionmentioning
confidence: 99%
“…Five of these compared health outcomes of nursing home residents in facilities that experienced a disaster compared with a control cohort of patients in facilities that did not experience a disaster. [30][31][32][33][34] Dosa et al 30 studied 30-day mortality, 90-day mortality, hospitalization rates, and measurements of functional decline for 9260 residents from 141 long-term care facilities in Louisiana and Mississippi that were impacted by Hurricane Katrina in 2005 and then compared the data with data for residents residing in the same facility during the 2 prior nonhurricane years (see Table S2 in the online data supplement). Many of these facilities evacuated.…”
Section: Health Effects Of Disaster Responsementioning
confidence: 99%